Fecundity and gonadosomatic index of Glossogobius giuris (Hamilton, 1822) from the Payra River, Patuakhali, Bangladesh - Md. Shakhawate Hossain; Animesh Roy; Mohammad Lutfar Rahman; Mohammad Abdus Salam; Mir Mohammad Ali (Journal of Fisheries, 2014)
Glossogobius giuris were collected during March to September 2013 from the Payra river to estimate the length-weight relationship with relative condition factor (Kn), fecundity, gonadosomatic index (GSI) and relation between fecundity and other parameters. The length-weight relationship was found to be Log W= 2.667 Log TL – 1.805 in male and Log W = 2.931 Log TL – 2.040 in female. The mean Kn were found to be 1.02±0.155 for male and 0.97±0.276 for female which indicates satisfactory condition of the fish population. The mean relative fecundity was ranged from 88495 to 264104 with a mean value of 171581±17855, having a average total length of 21.21±0.44 cm, body weight 70.22±4.62 g and gonad weight 2.74±0.31 g. The relationships among the fecundity, the total length, body weight, gonad weight were found to be linear and positively correlated. The mean GSI value was 3.42±0.33 and the highest GSI value was recorded 9.34±0.71 in the month of September. This study will help to introduce this species in sustainable aquaculture through proper management and for the development of induced breeding technique.